A Henry Wadsworth Longfellow companion - Gale, Robert L., 1919-2020. (Westport, Conn. : Greenwood Press, 2003)
Best remembered today as the author of The Song of Hiawatha, Longfellow continues to be one of the most popular poets in American literary history. This book is a guide to his life and writings. A brief introductory essay overviews Longfellow's life and accomplishments. A chronology then summarizes the chief events in his career. Hundreds of alphabetically arranged entries follow, discussing individual poems, his other writings, his family members and professional associates, and topics related to his life and literary achievements. Entries list works for further reading, and the volume closes.
Preface; Chronology; Short Titles of Works by Longfellow Cited; Short Titles of Critical and Biographical Works Cited; Abbreviations of Periodicals Cited in Which Longfellow Published; Entries; General Bibliography; Index.
Includes bibliographical references (pages 295-297) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Longfellow, Henry Wadsworth, -- 1807-1882 -- Criticism and interpretation -- Handbooks, manuals, etc; Longfellow, Henry Wadsworth, -- 1807-1882; Criticism, interpretation, etc; Handbooks and manuals